Stabilization of uncertain fuzzy time-delay systems via variable structure control approach. - Chong Lin (IEEE Transactions on fuzzy systems)
In view of a recent new application of variable structure control (VSC) to the stabilization problem for Takagi-Sugeno (T-S) fuzzy models, this paper aims to study the stabilization of uncertain fuzzy time-delay systems in T-S fuzzy model via VSC approach. There are mainly two features in this paper: one lies in the incorporation of time-delays (both smooth and nonsmooth delays) in which case Lyapunov functionals and Razumikhin Theorem are required to solve the stabilization problem; the other feature is that not only matched uncertainties but also mismatched uncertainties in the state variables are considered. As a sequence, the contribution of this paper consists of various control schemes proposed for the VSC design and the present results are in terms of linear matrix inequalities (LMIs). An illustrative example is given to show the effectiveness of our various results.